MECHANICAL PROPERTIES OF MULTI-AXIAL GLASS FIBER/MAH-WASTE KRAFTPAPER REINFORCED POLYESTER COMPOSITES - (:unkn) unknown (UNIV ZAGREB, FAC TEXTILE TECH, 2010)
The recovery and recycling of lignocelluloses fibers has experienced an important increase in the last years. In 2004, the apparent consumption of virgin cellulosic fibers for papermaking purposes was around 188 millions tones in all over the world. The apparent consumption of recovered paper in the world waste kraft papers and used paper products constitute a valuable source of fibers as raw material for conversion into high value composite materials, via dry processing methods, especially since waste kraft paper-reinforced plastic composites can be process similarly to wood-based composites. Nowadays, recycling of waste materials are coming into question place, so we used together waste material and multiaxial warp-knitting fabrics to make reinforced composite. In this study we investigated that maleic anhydride (MAH) modified recycled waste kraft paper/polyester resin/multi-axial warp knitted fabric composite structures. Composites were investigation tensile strength, strain, elasticity modulus and impact strength properties.
Keywords: maleic anhydride; composite; kraft paper; multi-axial warp knitted